Hubungan Leadership Competency dan Leadership Wisdom terhadap Trust pada Tenaga Pendidik dan Kependidikan P4TK Matematika Yogyakarta - Germino Wahyu Broto (Ta'allum: Jurnal Pendidikan Islam, 2015)
The current research is intended to (1) to find out the correlation between leadership competency of the leader and the trust of the staffs, (2) to find out the correlation between wisdom of the leader and the trust of the staffs, (3) to find out the correlation among leadership competency, wisdom and trust of the teaching staffs and administration staffs at P4TK Matematika Yogyakarta Ditjen PMPTK Depdiknas. The design of the research is model testing. The population is 100 people who are selected by using purposive sampling. The data are collected using leadership competency, leadership wisdom, and trust scales. The data are analyzed by using structural equation model (SEM) using Amos version 16. The findings reveal that (1) there is a correlation between leadership competency of the leader and trust of the staffs (γ= 0,651, dan ρ= 0,000), (2) there is a correlation between wisdom of the leader and the trust of the staffs (γ= 0,430, dan ρ= 0,000); (3) there is no correlation between leadership competency and leadership wisdom, (4) the correlation between leadership and trust of the staffs is stronger than the correlation between leadership and wisdom, (5) in group, leadership competency is correlated to trust. However, in isolation, leadership has no correlation with trust.